Characterizing the Human Mycobiota: A Comparison of Small Subunit rRNA, ITS1, ITS2, and Large Subunit rRNA Genomic Targets - Hoggard, Michael; Vesty, Anna; Wong, Giselle; Montgomery, Johanna M.; Fourie, Chantelle; Douglas, Richard G.; Biswas, Kristi; Taylor, Michael W. (Frontiers in Microbiology, 2018)
Interest in the human microbiome has increased dramatically in the last decade. However, much of this research has focused on bacteria, while the composition and roles of their fungal counterparts remain less understood. Furthermore, a variety of methodological approaches have been applied, and the comparability between studies is unclear. This study compared four primer pairs targeting the small subunit (SSU) rRNA (18S), ITS1, ITS2, and large subunit (LSU) rRNA (26S) genomic regions for their ability to accurately characterize fungal communities typical of the human mycobiota. All four target regions of 21 individual fungal mock community taxa were capable of being amplified adequately and sequenced. Mixed mock community analyses revealed marked variability in the ability of each primer pair to accurately characterize a complex community. ITS target regions outperformed LSU and SSU. Of the ITS regions, ITS1 failed to generate sequences for Yarrowia lipolytica and all three Malassezia species when in a mixed community. These findings were further supported in studies of human sinonasal and mouse fecal samples. Based on these analyses, previous studies using ITS1, SSU, or LSU markers may omit key taxa that are identified by the ITS2 marker. Of methods commonly used in human mycobiota studies to date, we recommend selection of the ITS2 marker. Further investigation of more recently developed fungal primer options will be essential to ultimately determine the optimal methodological approach by which future human mycobiota studies ought to be standardized.